Baccalaureate of nursing students’ experience of clinical accompaniment in e-distance learning (e-PJJ) / Suzana Yusof - Yusof, Suzana (2013)
Background: A qualitative, exploratory and descriptive study was conducted to explore the e-distance learning (e-PJJ) student nurses' experiences during clinical practice in the Intensive Care Unit (1CU). Objectives: The objectives of this study were: to explore the e-PJJ nursing students’ view regarding their clinical accompaniment during 1CU clinical placement and also to identify potential strategies towards the betterment of clinical accompaniment among UiTM e-PJJ nursing students during clinical placement. Methodology: Purposive sampling was used and in-depth interviews were held with eleven (11) student nurses who were in their final year of the four year basic nursing program. One focus group was held to validate the data. The interviews were transcribed into verbatim and analyzed. Qualitative methods included categorizing and coding were applied in this study. Results: The major findings of this study revealed that participants regarded that relationship and communication as important elements during clinical placement. They need minimal guidance from clinical nursing expert as they are all registered nurses. Conclusion: Nurse Educator / Clinical Instructor from faculty and nurse manager in the unit are expected to facilitate the nursing students during their clinical placement but there is no written guideline for them to follow in assisting those students. Recommendation: To develop a written guideline for students’ clinical accompaniment during clinical placement.